2009
DOI: 10.3348/jksr.2009.60.2.117
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the MRI and Integrated PET/CT Findings in the Preoperative Detection of Peritoneal Carcinomatosis Arising from Primary Ovarian Cancer

Abstract: Purpose:To compare the diagnostic performance of MRI and integrated PET/CT for the preoperative detection of peritoneal carcinomatosis arising from primary ovarian cancer. Materials and Methods: Twenty-three patients with suspected ovarian tumors underwent a contrast-enhanced 1.5 Tesla MRI and a 18F-fluorodeoxyglucose (FDG) PET/CT prior to surgery. The peritoneal cavity was subdivided into six specific sites for a lesion-based analysis. The imaging findings were compared statistically with the histopathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…MRI and spiral CT show similar accuracy in the detection of PC and PC size, spread and localization compared to CT. In a study by Kim et al it is showed that MRI achieves a sensitivity of 95% [ 30 ]. The mandatory long hold of breath proves to be difficult for many patients with tumors due to their generally weak condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI and spiral CT show similar accuracy in the detection of PC and PC size, spread and localization compared to CT. In a study by Kim et al it is showed that MRI achieves a sensitivity of 95% [ 30 ]. The mandatory long hold of breath proves to be difficult for many patients with tumors due to their generally weak condition.…”
Section: Discussionmentioning
confidence: 99%
“…The mandatory long hold of breath proves to be difficult for many patients with tumors due to their generally weak condition. This could lead to evaluation artifacts and diminish the quality of MRI depiction [ 30 ]. Another disadvantage is the existence of ascites which could also lead to artifacts using MRI and could often be the reason for high wrong positive-rates [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…18 F-FDG uptake in EOPPC was described initially in two small studies, however the pattern of FDG uptake was not described, and no distinction was made in the imaging characteristics between EOPPC and EOC patients [3,4]. Subsequent larger studies examining the role of 18 F-FDG PET or PET/CT in the evaluation of peritoneal carcinomatosis did not include any EOPPC patients [2,[25][26][27][28][29][30]. To date, the 18 F-FDG PET/CT imaging characteristics of EOPPC have never been described and the possibility of differentiating EOPPC from EOC based on patterns of 18 F-FDG distribution has not been investigated.…”
Section: Discussionmentioning
confidence: 97%
“…18 Kim CK et al (2009) have done a comparative study of MRI and integrated PET/CT for the preoperative detection of peritoneal carcinomatosis arising from primary ovarian cancer in 253 patients and has concluded that patient-based sensitivity, specificity and accuracy of the use of MRI versus PET/CT for the detection of peritoneal carcinomatosis were 95% versus 84%, 50% versus 50% and 87% versus 78% respectively. 19 Moreover, the comparison of the lesion-based sensitivity, specificity and accuracy of MRI versus integrated PET/CT were 86% and 75% , 76% and 84% , and 82% and 78% , respectively concluding that MRI was more sensitive that PET/CT for detection of peritoneal carcinomatosis.…”
Section: Comparative Studies On Usg Ct/mri Correlated With Surgico-pmentioning
confidence: 90%